Gambaran Obesitas pada Penderita Hipertensi di Puskesmas Gondangrejo - Yeni Puji Astuti; Ika Silvitasari (Pusat Riset dan Inovasi Nasional, 2025)
Background: Obesity can exacerbate blood pressure and increase the risk of cardiovascular complications, including hypertension. Hypertension is a disease with an increasing prevalence each year, particularly among individuals from the productive age group to the elderly. Objective: This study aimed to describe the prevalence of obesity among hypertensive patients at the Gondangrejo Public Health Center. Methods: This study employed a descriptive quantitative method with a cross-sectional design. The sampling technique used was incidental sampling, which involved 62 respondents. Data were collected through direct observation, observation sheets and documentation. Results: The findings showed that the majority of respondents were in late adulthood (45–59 years old), totaling 35 individuals, with 41 of the respondents being female. Most of the participants were housewives (22 respondents). Blood pressure levels were categorized as Stage I Hypertension, while obesity levels were predominantly classified as Obesity Class I. Conclusion: The study concluded that middle-aged adult females, particularly housewives with Stage I Hypertension and Obesity Class I, constitute the dominant profile of hypertensive patients at the Gondangrejo Public Health Center.